A Tropical Macroalga (Halimeda incrassata) Enhances Diversity and Abundance of Epifaunal Assemblages in Mediterranean Seagrass Meadows - Mateo-Ramírez, Ángel; Máñez-Crespo, Julia; Royo, Laura; Tuya, Fernando; Castejón-Silvo, Inés; Hernan, Gema; Pereda-Briones, Laura; Terrados, Jorge; Tomas, Fiona (Frontiers in Marine Science, 2022)
The introduction and successful expansion of tropical species into temperate systems is being exacerbated by climate change, and it is particularly important to identify the impacts that those species may have, especially when habitat-forming species are involved. Seagrass meadows are key shallow coastal habitats that provide critical ecosystem services worldwide, and they are threatened by the arrival of non-native macroalgae. Here, we examined the effects of Halimeda incrassata, a tropical alga that has recently colonized the Mediterranean Sea, on epifaunal assemblages associated with Cymodocea nodosa seagrass meadows of Mallorca Island (Western Mediterranean Sea). This invasive macroalga is an ecological engineer and thus has a high potential of modifying native habitats. A seagrass meadow colonized by H. incrassata exhibited important changes on associated epifaunal assemblages, with an increase in abundance and diversity, particularly driven by higher abundances of Gammaridae, Polychaeta, Copepoda and Caprellidae. Given the key ecological contribution of epifauna to food webs, these alterations will likely have important implications for overall food web structure and ecosystem functioning of native ecosystems.